Quantification and normalization of x-ray mammograms. - Tromans, C; Cocker, MR; Brady, S (2012)
The analysis of (x-ray) mammograms remains qualitative, relying on the judgement of clinicians. We present a novel method to compute a quantitative, normalized measure of tissue radiodensity traversed by the primary beam incident on each pixel of a mammogram, a measure we term the standard attenuation rate (SAR). SAR enables: the estimation of breast density which is linked to cancer risk; direct comparison between images; the full potential of computer aided diagnosis to be utilized; and a basis for digital breast tomosynthesis reconstruction. It does this by removing the effects of the imaging conditions under which the mammogram is acquired. First, the x-ray spectrum incident upon the breast is calculated, and from this, the energy exiting the breast is calculated. The contribution of scattered radiation is calculated and subtracted. The SAR measure is the scaling factor that must be applied to the reference material in order to match the primary attenuation of the breast. Specifically, this is the scaled reference material attenuation which when traversed by an identical beam to that traversing the breast, and when subsequently detected, results in the primary component of the pixel intensity observed in the breast image. We present results using two tissue equivalent phantoms, as well as a sensitivity analysis to detector response changes over time and possible errors in compressed thickness measurement.